Winter birds which might be of interest, December 1, 1977 to February 9, 1978 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1977)
Field notes titled "Winter birds which might be of interest," December 1, 1977 to February 9, 1978, " submitted by Thomas H. Kent to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed